Analysis of Nasakh Mansukh in the Hadith of Pilgrimage to the Grave - April Liana Citra Imanniar; Romlah Abubakar; Miftahuddin Miftahuddin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The hadith on grave visitation stands as one of the clearest examples of abrogation (nasakh) occurring within the prophetic tradition. In the early period of Islam, the Prophet Muhammad SAW prohibited his followers from visiting graves out of concern that such practice would lead to excessive veneration of graves, given that the community had only recently left behind the deeply rooted customs of the pre-Islamic era (jahiliyyah). As the foundation of monotheism grew stronger among Muslims, the prohibition was lifted and replaced with a directive that not only permitted but actively encouraged the practice of grave visitation. This study traces two central points: first, the shift in the legal ruling on grave visitation from prohibition to permissibility is examined through the lens of nasakh-mansukh within the science of hadith; second, the validity of that legal shift is assessed against the conditions of abrogation established in hadith sciences. This study employs a qualitative approach grounded in library research, drawing on the disciplines of hadith sciences and usul al-fiqh. The findings indicate that the prohibitory hadith on grave visitation holds the status of mansukh, having been legitimately replaced by the permissive hadiths upon the fulfillment of all conditions for valid abrogation. This abrogation was explicitly confirmed by Imam al-Nawawi, who stated that this constitutes a clear and evident case of abrogation, and that scholars are in consensus that grave visitation carries the status of sunnah.